2011
DOI: 10.1074/jbc.m110.198804
|View full text |Cite
|
Sign up to set email alerts
|

MSH3 Mediates Sensitization of Colorectal Cancer Cells to Cisplatin, Oxaliplatin, and a Poly(ADP-ribose) Polymerase Inhibitor

Abstract: The MSH3 gene is one of the DNA mismatch repair (MMR) genes that has undergone somatic mutation frequently in MMRdeficient cancers. MSH3, together with MSH2, forms the MutS␤ heteroduplex, which interacts with interstrand cross-links (ICLs) induced by drugs such as cisplatin and psoralen. However, the precise role of MSH3 in mediating the cytotoxic effects of ICLinducing agents remains poorly understood. In this study, we first examined the effects of MSH3 deficiency on cytotoxicity caused by cisplatin and oxal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 40 publications
1
78
1
Order By: Relevance
“…Therefore, caution must be exerted in interpreting the lower staging and the better outcome of cancers with MSH3 loss as the result of a more severe mutator phenotype, as protein loss or gene inactivation might directly affect tumor progression in the absence of any effect on MMR efficiency. Along this line, MSH3 deficiency has been recently shown to sensitize CRC cells to platinum drugs independently of any influence on the canonical MMR system (53).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, caution must be exerted in interpreting the lower staging and the better outcome of cancers with MSH3 loss as the result of a more severe mutator phenotype, as protein loss or gene inactivation might directly affect tumor progression in the absence of any effect on MMR efficiency. Along this line, MSH3 deficiency has been recently shown to sensitize CRC cells to platinum drugs independently of any influence on the canonical MMR system (53).…”
Section: Discussionmentioning
confidence: 99%
“…We found no changes in the response of pancreatic cancer cells with altered RABL6A expression to treatment with gemcitabine, 5-FU, or irinotecan, whereas RABL6A loss selectively sensitized cells to oxaliplatininduced cell arrest and apoptosis. Only a few genes have been identified that influence the cellular response to oxaliplatin, including ERCC1, 29 MSH3, 30 survivin, 31,32 and NF-kB. 31 Notably, those studies were performed in other cancer cell types and the importance of those genes to PDAC is not established.…”
Section: Discussionmentioning
confidence: 99%
“…HCT116 cells that were MMR-corrected by transfer of chromosome 3 (HCT116ϩChr.3) or transfer of chromosomes 3 and 5 (HCT116ϩChr.3ϩ5) were gifted by Ajay Goel (39). All cells were grown in McCoy's 5A medium with 10% fetal bovine serum (FBS), penicillin (100 units/ml), and streptomycin (100 g/ml).…”
Section: Methodsmentioning
confidence: 99%